Resettlement Programme for Landless Agricultural Labourers Case Studies of Selected Colonies PEO Pub. No. 61 - Planning Commission (Planning Commission, 1968)
Agricultural development and rural reconstruction has been the corner-stone of Development Planning. Series of land reform measures releasing surplus lands above ceiling, reclamation of culturable waste lands, Bhoodan and Gramdan movement have been the various measures through which programme of land settlements have been effected for the benefit of backward sections of the community specially the landless agricultural labourers. Resettlement programmes which had been undertaken during all the Plans, received pointed emphasis with the Centrally Sponsored schemes initiated during the Third Plan. With a view to study the problems of resettlement and its impact, the Programme Evaluation Organisation, at the instance of Planning Commission, took up a study of Resettlement of Agricultural Labourers in 1966. The said study was confined to only colonisation settlements and was undertaken in seven districts located in as many States. Reports in respect of each district are presented separately in Part II with an overall write-up in Part I. the thirteen colonisation settlements under study reveal different scales of efforts and variety of contents and coverage and it is hoped that the analysis, as presented in this report, will help in improving the performance of the programme.
Programme Evaluation Organisation Planning Commission Government of India